2020
DOI: 10.1002/brb3.1907
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral autoregulation is heterogeneous in different stroke mechanism of ischemic stroke caused by intracranial atherosclerotic stenosis

Abstract: Background and Purpose Intracranial atherosclerotic stenosis (ICAS) is the most common cause of ischemic stroke (IS) and is associated with stroke recurrence. It results in IS due to a variety of mechanisms. However, the influence of brain reserve mechanism on different stroke mechanism is still unclear. Cerebral autoregulation (CA) is an important brain reserve mechanism and is impaired after IS. This study aimed to explore the impaired pattern of CA and assess the association between CA and stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…During the pre-CEA phase, we observed that the highest correlation greater than 0.3 was in the SH group on the ipsilateral hemisphere ( Figure 6 , SH group). Since the shunt utilization was decided either intraoperatively based on EEG changes or pre-surgically based on the patient’s stroke history and neurological evaluation, ipsilaterally weakened CAR in the SH group during this phase may reflect the degrees of their past ischemic stroke or transient ischemic attacks [ 37 , 38 ]. The better CAR in the SCS group than in other groups during the pre-CEA phase may actually be an indication of the ability to maintain constant CBF i for elevated MAP ( Figure 6 , p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…During the pre-CEA phase, we observed that the highest correlation greater than 0.3 was in the SH group on the ipsilateral hemisphere ( Figure 6 , SH group). Since the shunt utilization was decided either intraoperatively based on EEG changes or pre-surgically based on the patient’s stroke history and neurological evaluation, ipsilaterally weakened CAR in the SH group during this phase may reflect the degrees of their past ischemic stroke or transient ischemic attacks [ 37 , 38 ]. The better CAR in the SCS group than in other groups during the pre-CEA phase may actually be an indication of the ability to maintain constant CBF i for elevated MAP ( Figure 6 , p = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…From a vascular perspective, alterations in G protein signaling involving monoamines such as adrenaline, noradrenaline, serotonin, dopamine, and histamine could be directly associated with cerebral hypoperfusion, a well-known imaging hallmark of neurodegenerative diseases [21,51,52]. Cerebral hypoperfusion is also a common risk factor in cerebrovascular diseases such as cerebral microbleeds and stroke [53,54]. Therefore, G i PCR-driven signaling for the maintenance of CBF may be relevant to identify novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional DSA images can be considered in future QFR computation. Notably, autoregulation and collateral circulation further complicate the cerebral hemodynamic status (Tian et al, 2021). More studies were required to continuously improve the method of QFR computation.…”
Section: Discussionmentioning
confidence: 99%